Challenges in Managing Metabolic Syndrome in Psoriasis: A Narrative Review of Pharmacological and Surgical Treatments - Aleksandra Bętkowska; Stanisław Dudek; Weronika Koziak; Michalina Makieła; Agata Kornacka; Wojciech Dudek; Kamila Szostak; Marta Makieła; Rafał Tomaka; Daniel Worobiej (Quality in Sport)
Introduction: Psoriasis is a chronic inflammatory disorder associated with multiple systemic comorbidities, most notably metabolic syndrome, which affects approximately one-third of individuals with the disease. Metabolic syndrome—characterized by obesity, insulin resistance, dyslipidemia, and hypertension—exacerbates systemic inflammation, further complicating disease management and treatment outcomes.